Judges' Considerations in Deciding on Marriage Dispensation Cases at Religious Courts in Lampung Province, Indonesia - Iwannudin, Iwannudin (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article discusses the granting of marriage dispensation which is given in order to provide legal certainty to conduct marriages outside the age limit of marriage. While some sources state that marriage at a young age has a negative impact. The purpose of this article is to analyze the basis of the judge's argument in deciding the marriage dispensation case from a benefit perspective. This article is a field research, by examining the decisions of judges at the Religious Court in Lampung Province in 2022, primary sources are then analyzed qualitatively, analyzed based on the theory of legal sociology and benefits. The results of the analysis found that the basis of the judge's argument in the marriage dispensation case is several laws and regulations, and the principles of Islamic law. If the judge's decision only focuses on granting dispensation and imposing court costs, then the decision is inappropriate, because the judge's legal considerations are basically only based on the marriage law without considering other laws related to children such as Law No. 4 of 1979 concerning Child Welfare, Law No. 23 of 2002 concerning Child Protection. Based on the theory of Maqosid Syariah, the decision in question is less useful, because it only gives the impression of legal certainty to obtain marriage dispensation, without any certainty that the rights of children will be guaranteed in the future. The implications of the results of this study are as study material and consideration in the renewal of family law.Keywords: Legal Basis, Decision of Marriage Dispensation Judge, Maslahat